Identifying limiting factors for feasible productivity improvement for smallholder farmers in coffee sector in Indonesia (Asian Journal of Agriculture, 2021)
Abstract. Tran HTM, Nathan S, Ilmma A, Burkiewicz M, Wisana IDGK. 2021. Identifying limiting factors for feasible productivity improvement for smallholder farmers in coffee sector in Indonesia. Asian J Agric 5: 53-60. Coffee is a global commodity with significant value-addition and export potential for producing countries. The purpose of this study was to identify the important factors associated with increasing yields. Rather than prescribing theoretical solutions, our research purpose was to examine the prevailing agricultural practices that are used in the region and identify the top three factors that have a significant impact on yields. Using advanced data collection methods and controlling for regional characteristics and various farming practices, we found that higher yield was associated with the application of fertilizer, higher tree density, and shade level. The application of fertilizer was associated with an increase in yield of 98 kg/ha for Arabica and 124 kg/ha for Robusta. At the optimal density ranges, a higher yield can be obtained with the increase of trees. Lastly, the level of shade was negatively associated with yield for Arabica, but no significant difference was observed for Robusta. We found a lot of headroom to increase the yield, as the current fertilizer application was low especially for Robusta, a mismatch between optimum tree density for both Arabica and Robusta, and opportunities for better shade management to increase yield potential.
Keywords: coffee; density; fertilizer; shade; yield